Investigation of Ecological and Economical Characteristics of Systems of Gas Outburst Cleaning from Dioxide Sulphur - V. P. Bubnov; D. A. Dovnar (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2013)
The paper presents the ecological and economical characteristics of different ways for purifying of waste gases from sulfurous anhydride (SO2).And proved that the least expenditures for purification of 1000 m3 have: lime and limestone, but also electron beam Methods. But, electron beam Method allow at the same time to carry out the purification of smoke gases from SO2 and NOх.